Fernald Method in Differentiated Learning for Early Reading of Science Texts: Metode Fernald dalam Pembelajaran Berdiferensiasi untuk Membaca Awal Teks Sains - S, Ismayanti; Pujaningsih (Indonesian Journal of Innovation Studies, 2025)
General Background: Inclusive education in Indonesia has been mandated through national regulations, yet its implementation faces challenges, particularly in addressing reading difficulties among students with learning disabilities. Specific Background: Reading is the foundation of all learning, but many seventh-grade students at SMP Negeri 6 Sangatta Utara still struggle with basic reading skills, limiting their comprehension of science texts. Knowledge Gap: While the Fernald multisensory method has shown effectiveness internationally, limited studies in Indonesia have explored its application in science learning contexts for middle school students with reading difficulties. Aims: This study investigates the effectiveness of the Fernald method, integrated within differentiated instruction, in improving early reading skills of students with learning disabilities. Results: Conducted through Classroom Action Research in two cycles, the intervention revealed significant improvement: students’ scores increased from 20–40% in the pre-test to 90–100% in the post-test, alongside higher participation and confidence levels. Novelty: This research demonstrates the contextualized application of the Fernald method for science literacy at the junior high school level in Indonesia, emphasizing differentiated multisensory strategies. Implications: The findings suggest that Fernald’s method can serve as an effective alternative for inclusive classrooms, supporting teachers in fostering literacy, motivation, and engagement among diverse learners.Highlight : The Fernald Method is effective in improving early reading skills. A multisensory approach supports mastery of letters and words. Student participation and motivation increase in learning. Keywords : Inclusive Education, Reading Difficulties, Fernald Method, Differentiated Learning, Multisensory